2015
DOI: 10.18632/oncotarget.3752
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin inhibits vasculogenic function of endothelial progenitor cells in tumor progression and metastasis via suppression of focal adhesion

Abstract: Deguelin is a nature-derived chemopreventive drug. Endothelial progenitor cells (EPCs) are bone-marrow (BM)-derived key components to induce new blood vessels in early tumorigenesis and metastasis. Here we determined whether deguelin inhibits EPC function in vitro and in vivo at doses not affecting cancer cell apoptosis. Deguelin significantly reduced the number of EPC colony forming units of BM-derived c-kit+/sca-1+ mononuclear cells (MNCs), proliferation, migration, and adhesion to endothelial cell monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…We confirmed through this study that HK2 is overexpressed in NSCLC cell lines and lung cancer tissues (Figure 1), which implied that HK2 may has a crucial role during lung tumorgenesis. Recently, some natural compounds, such as resveratrol [39] and EGCG [40, 41], have been demonstrated to inhibit hepatocellular carcinoma or oral cancer via directly targeting glycolysis. These findings implied that decreases of glycolysis or inhibits of metabolic enzymes may act as one of the major mechanisms in natural compound mediated anti-tumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed through this study that HK2 is overexpressed in NSCLC cell lines and lung cancer tissues (Figure 1), which implied that HK2 may has a crucial role during lung tumorgenesis. Recently, some natural compounds, such as resveratrol [39] and EGCG [40, 41], have been demonstrated to inhibit hepatocellular carcinoma or oral cancer via directly targeting glycolysis. These findings implied that decreases of glycolysis or inhibits of metabolic enzymes may act as one of the major mechanisms in natural compound mediated anti-tumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the protagonists of inter-cellular adhesion are not yet identified in the here presented 3D model. Whether NF-kB and ICAM-1 establish CRC-CAF adhesion, as shown to be the case in 12(S)-HETE-triggered breast cancer/EC intravasation [14, 19], needs to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the induction of MLC2 phosphorylation and CCID formation is not exclusively caused by the 12(S)-HETE gradient, as there are also other factors prompting tropism and retraction i.e. MMP1, which induces Ca 2+ release and MLC2 activation in ECs as well [19, 46]. Yet, treating the CRC/CAF model with the pan-matrix metalloprotease inhibitor GM6001 did not inhibit the formation of CCIDs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, one study has found that deguelin, a chemopreventive drug, can reduce the number of colony-forming units of bone marrow-derived c-Kit + /Sca-1 + mononuclear cell migration, adhesion, and proliferation capability. When cocultured with endothelial cells, the treated EPC were less likely to form tubelike vessels, because deguelin arrested the cells at the G 1 checkpoint 42. In Moyamoya disease (MMD), a form of childhood stroke, the expression of retinaldehyde dehydrogenase 2 is significantly reduced in ECFCs, rendering them less efficient in forming capillary networks in vitro as well as in vivo 43.…”
Section: Cell-based Therapy: the Next Generation Of Rop Treatment?mentioning
confidence: 99%